Fifth Generation Mobile Communication Technology Network Attack Defense Based on Software Defined network Technology in Power Internet of Things - Li, Tong; Zhao, Hai; Song, Shouyou; Yang, Chao; Du, Chunlai; Liu, Yang (Frontiers in Energy Research, 2022)
The purpose is to guarantee the security of fifth generation mobile communication technology (5G) network in power Internet of Things environment and improve the ability of wireless network communication to resist attacks. First, in terms of attack prevention, the 5G network security structure is proposed to replace the plaintext information commonly used in the original system with Ciphertext based on software defined network (SDN), thereby alleviating the security risks of the data dimension. Second, concerning attack detection, the signal is identified by using the imperfections and differences of equipment manufacturing based on the above security structure, preventing the attacker from further harming the sensitive data leaked. Researchers found that the SDN-based 5G network attack prevention scheme avoids the centralized exposure of sensitive data, improves security, reduces computational overhead, and simplifies encryption logic. Without affecting the bandwidth, the existing 5G network system is greatly prevented from attacks. The detection mechanism is not limited by the low-dimensional feature space, and it demonstrates strong robustness and stability. It can effectively detect the attacks on 5G network system in power Internet of Things (IoT). This study provides an important reference for the protection of 5G communication network attacks under IoT.